Von der Frühverrentung bis zur Rente mit 67 Der Wandel des Altersübergangs von 1990 bis 2012 - Brussig, Martin (Forschung aus der Hans-Böckler-Stiftung, 2016)
25 years ago there was still forced early retirement. Today, working life is drawn out for as long as possible: this book explains how this paradigm shift in aged employment came about.